Age Effects in Education: A Double Disadvantage for Second-Generation Immigrant Children - Antonio Abatemarco; Mariagrazia Cavallo; Immacolata Marino; Giuseppe Russo (Global Labor Organization (GLO), 2021)
A double disadvantage occurs when the interaction of two disadvantages generates an additional disadvantage. We show that second-generation immigrant children in the Italian primary school experience a double disadvantage that, relative to the average native, reduces scores in Italian by 17% and in Math by 20%. The double disadvantage stems from the interaction of the immigration background with age effects (namely, Absolute Age Effect and Relative Age Effect). In a policy perspective, we show that controlling for age effects in class composition criteria pursues integration because it delivers extra benefits to second-generation immigrant children. Besides, we point out the possibility of exploiting the larger impact of the relative age on second-generation children in order to support their performance and reduce the large penalization associated to the immigration background.
Keywords: I21; J01; J13; Z13; 330; second-generation immigrants; education; age effects; double disadvantage